Pengaruh Manajemen Pelayanan Terhadap Kinerja Pegawai Di Kantor Sekretariat Dewan Kabupaten Enrekang - Syah, Alfin Firman; Hakim, Lukman; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2021)
This study aims to: determine service management at the Secretariat Office of the Enrekang Regency Council, determine the performance of employees at the Enrekang Regency Council Secretariat Office, and determine the effect of service management on employee performance at the Enrekang Regency Council Secretariat Office. Data collection using a questionnaire that was distributed to 50 employees. The data analysis used descriptive analysis and simple linear regression analysis. The results showed that: service management was in good category with performance appraisal as the most prominent aspect, employee performance was in good category with the most prominent aspect of responsibility and service management had a positive and significant effect on the performance of the employees of the Enrekang Regency Council Secretariat office. Thus, the higher the service management provided, the higher the employee's performance. Through performance, it is known the level of achievement of the results that have been achieved, or it will be known how far the implementation of tasks has been carried out. Keywords: Service Management, Employee Performance.